Simulation of boost AC-AC converter using single-phase matrix converter - Zeynep Bala Duranay; Hanifi Guldemir (International Journal of Applied Power Engineering (IJAPE), 2021)
Generally, AC-AC converters are implemented using thyristors. These converters generate harmonics and have a low power factor. To eliminate these problems matrix converters (MC) are become used as AC-AC converter. Matrix converters have the capability of being used as frequency changer, rectifier, inverter and chopper. In this work, it is proposed to achieve the desired output of AC-AC Boost converter using single phase matrix converter (SPMC). The operation of single-phase AC-AC boost converter using MC is studied in this paper. The output voltage of this boost converter is higher than the AC input supply voltage. insulated gate bipolar transistors (IGBTs) are used as the switching elements in the SPMC power circuit. Sinusoidal Pulse width modulation (SPWM) technique is applied to generate switching signals to obtain the output voltage. The model of the matrix converter is constructed in MATLAB/Simulink programming software package. The behavior of SPMC is simulated with various switching frequencies. The simulation results together with harmonic spectrum and total harmonic distortion (THD) values are presented. Successful operation of boost SPMC is achieved.